ANALISIS KEDUDUKAN MEJELIS KEHORMATAN MAHKAMAH KONSTITUSI DALAM KELEMBAGAAN MAHKAMAH KONSTITUSI - Kartika, Kartika; Artina, Dessy; Junaidi, Junaidi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Judicial power is independent power to administer justice to uphold lawand justice. One of the institutions of judicial power is the Constitutional Court(MK). In carrying out their duties, a judge must comply with the Code of Ethicsfor Constitutional Judges, therefore, a supervisory institution for constitutionaljudges is needed in carrying out their duties. In the state institution system, theinstitution authorized to supervise the independence of judges within the judiciaryis the Judicial Commission (KY). Constitutional judges were actually once theobject of KY supervision, but since MK Decision Number 005/PUU-IV/2006, theKY's authority to supervise constitutional judges has been decided to beunconstitutional. So the Constitutional Court Honorary Council (MKMK) wasformed as an internal supervisory institution formed by Constitutional Justices.This research can be classified into a type of normative legal researchrelated to Constitutional Court Regulations. Then use data sources from primary,secondary and tertiary legal materials by conducting literature studies incollecting data and using qualitative analysis methods in processing data anddrawing conclusions.From the results of research that has been carried out, this internalsupervision institution is considered ineffective due to the lack of transparencyand neutrality of the supervision carried out. Based on these studies, neutrality inthe formation of supervisory institutions is very necessary to form an idealsupervision mechanism based on Sapta Karsa Utama.Keywords: Position, MKMK, Establishment